Development of a new drug for progeria syndrome; Past, Present and Future - So-mi Kang; Minju Kim; Bum-Joon Park (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2020)
Hutchinson-Gilford progeria syndrome (HGPS) is the best characterized genetic disorder with premature aging features. Classic HGPS is very rare, sporadic orphan disease, inherited in an autosomal dominant manner without gender or ethnic differences. Children with HGPS appear normal at birth, but begin to develop segmental progeroid symptoms within the first years of life. Patients suffer from sarcopenia, lipodystrophy, diabetes, cataracts, atherosclerosis but not cancer and neurodegenerative diseases. Genetic factors that are associated with this syndrome have been identified, mouse models of disease have been developed, and clinical studies have been conducted for many years. Although many medical and treatment approaches were implemented and showed some efficacy, these therapies could not be considered as a complete cure, and more effective therapeutic approaches were needed for HGPS patients. This report introduces a novel drug called progerinin, which is a binding inhibitor of lamin A and progerin, for patients affected with HGPS.